2017
DOI: 10.3847/2041-8213/aa7046
|View full text |Cite
|
Sign up to set email alerts
|

First Millimeter Detection of the Disk around a Young, Isolated, Planetary-mass Object

Abstract: OTS44 is one of only four free-floating planets known to have a disk. We have previously shown that it is the coolest and least massive known free-floating planet (∼12 M Jup ) with a substantial disk that is actively accreting. We have obtained Band 6 (233 GHz) ALMA continuum data of this very young disk-bearing object. The data show a clear unresolved detection of the source. We obtained disk-mass estimates via empirical correlations derived for young, higher-mass, central (substellar) objects. The range of v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 48 publications
(68 reference statements)
1
30
2
Order By: Relevance
“…Silk 1977;Bowler et al 2011). In fact, Fang et al (2016); Luhman et al (2005); Boucher et al (2016);Joergens et al (2015); Bayo et al (2017) have found four FFPs with accretion disk. Furthermore, planetary-mass binaries, which would be almost impossible to from through planetary formation mechanisms, have also be found by e.g.…”
Section: Erik Elfgrenmentioning
confidence: 99%
“…Silk 1977;Bowler et al 2011). In fact, Fang et al (2016); Luhman et al (2005); Boucher et al (2016);Joergens et al (2015); Bayo et al (2017) have found four FFPs with accretion disk. Furthermore, planetary-mass binaries, which would be almost impossible to from through planetary formation mechanisms, have also be found by e.g.…”
Section: Erik Elfgrenmentioning
confidence: 99%
“…If there is ALMA detection of discs around planetary mass objects, we can use our disc models to constrain CPD properties. We take the recent ALMA detection of the disc around OTS44 (a 12MJ object) as an example (Bayo et al 2017). OTS44 accretes at 8×10 −12 M⊙/yr.…”
Section: Constraining Cpd Propertiesmentioning
confidence: 99%
“…2.2 in Pinilla et al 2013). It is, however, evident that disks around VLM stars and BDs host millimeter sizedparticles (Ricci et al 2014;Bayo et al 2017;Pinilla et al 2017b) and that somehow the radial drift of the particles is reduced or completely suppressed in these disks.…”
Section: Introductionmentioning
confidence: 99%